Sorafenib as first-line treatment for patients with primary hepatocellular carcinoma: an outcome evaluation - Dung Thi Nguyen; Duong Hoang Nguyen; Van Thi Hong Nguyen (Journal of International Medical Research, 2023)
Objective To evaluate the clinical outcomes following first-line treatment with sorafenib in patients with primary hepatocellular carcinoma (HCC). Methods This retrospective cohort study enrolled patients with primary HCC that had been treated with sorafenib. Their data were collected from the hospital medical records database at three time-points: after three cycles, after six cycles and at the end of the sorafenib treatment regimen. The starting dose was 800 mg/day sorafenib but this could be reduced to 600 mg/day or 400 mg/day if patients developed adverse events (AEs). Results A total of 98 patients participated in the study. Of these, nine (9.2%) had a partial response, 47 patients (48.0%) had stable disease and 42 patients (42.9%) had progressive disease. The overall disease control rate was 57.1% (56 of 98 patients). Median progression-free survival for the overall cohort was 4.7 months. The most common AEs were hand-foot skin reaction (49 of 98 patients; 50.0%), fatigue (41 of 98 patients; 41.8%), appetite loss (39 of 98 patients; 39.8%) and hepatotoxicity/transaminitis (24 of 98 patients; 24.5%). The majority of the AEs were toxicity grades 1 and 2. Conclusion Sorafenib as a first-line treatment for primary HCC patients provided survival benefits and the AEs were well tolerated by patients.